Synthesis of Nanofiltration Membrane Developed from Different Concentration of Triethanolamine (TEOA) for Separation of Xylose from Glucose - Nurul Fatihah, Mahamad Roli; Wan Mohd Hafizuddin, Wan Yussof; Syed Mohd Saufi, Tuan Chik; Mazrul Nizam, Abu Seman; Abdul W., Mohammad (2015)
Synthesis of thin film composite (TFC) nanofiltration membrane has experienced tremendous development since the concept of interfacial polymerization (IP) was first introduced. One of it new application is on the separation of xylose from glucose in biomass hydrolysate. In this present study, thin film composite (TFC) nanofiltration (NF) membrane has been produced through interfacial polymerization by manipulation the concentration of triethanolamine (TEOA) at different reaction time with 0.15 % w/v. of trimesoyl chloride (TMC). The membrane was then characterized in term of their chemical and physical properties, and separation performance between xylose and glucose. The growth of thin layer film depends on concentration of the monomer (TEOA) and reaction time. It was found that as concentration of TEOA and reaction time increased, the layer of the TFC become thicker thus decreases the permeability of the membrane. In contrast, the lowest and the highest permeability were recorded at 4% w/v of TEOA and 8% w/v of TEOA at reaction time of 35-minute in TMC, respectively. Moreover, higher sugar rejection of 0.896 % was obtained at 4% w/v TEOA after 35-minute reaction in TMC.